The Formation of Democracy and Social Thought in Hungary - Kovacs, Margit (Problemos, 1984)
A study of democracy and social activity development presupposes an analysis of how the economic basis of socialist society stimulates and conditions the development of social life. The task is undertaken in the article, (a) to trace the reciprocal influence of the development of socialist relations of production and the relations existing in the field of superstructure, and (b) to analyse the structure of socialist democracy and dynamics of its forms against file background of ideological and socio-psychological processes arising in the present stage of socialist construction. Research materials of both Hungarian and Soviet authors were made use of in the article.